2015
DOI: 10.1080/13607863.2014.922528
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antimuscarinic therapy on cognitive functions and quality of life in geriatric patients treated for overactive bladder

Abstract: Antimuscarinic agents are effective in OAB treatment. They have a positive impact on daily life activities, depression, and QOL indices. Furthermore, they do not have a negative effect on cognitive function in older adults with or without AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…We calculated the SMD of global cognitive decline for six studies [ 11 , 14 , 31 , 36 , 38 , 46 ]: five studies reported MMSE, while one calculated a composite score from 19 cognitive tests [ 38 ]. All but one study adjusted for some potential confounders [ 31 ]. Greater cognitive decline was consistently observed among patients taking anticholinergic drugs (SMD 0.15; 95% CI 0.09–0.21, I 2 = 3%) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We calculated the SMD of global cognitive decline for six studies [ 11 , 14 , 31 , 36 , 38 , 46 ]: five studies reported MMSE, while one calculated a composite score from 19 cognitive tests [ 38 ]. All but one study adjusted for some potential confounders [ 31 ]. Greater cognitive decline was consistently observed among patients taking anticholinergic drugs (SMD 0.15; 95% CI 0.09–0.21, I 2 = 3%) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In two longitudinal studies involving older patients aged 65 and above, depression at baseline predicted new onset urgency incontinence at the 1-year follow up in one study and at the 6-year follow up in the second study [ 19 , 20 ]. Studies in the clinical OAB population showed that depression improved with successful treatment of OAB with anticholinergic medications, botulinum toxin A, and InterStim neuromodulation [ 21 23 ]. Collectively these studies suggested a causality relationship between depression and OAB/incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and radioligand binding studies have determined that tolterodine has a high potential for CNS penetration [ 55 , 56 ]. However, the results of a clinical study showed that the incidence of cognitive impairment was not significantly higher than that in the control group [ 65 ].…”
Section: Anticholinergicsmentioning
confidence: 99%